Harrismatrix.com : home of archaeology's premier stratigraphy system - National Museum of Bermuda (2004)
[Dt.:] Auf der Website gibt es Informationen, eine Einführung und eine Bibliographie zur Harris Matrix, welche es Archäologen ermöglicht stratigraphische Informationen in Diagrammform darzustellen. - [Engl.:] The web site contains information, an introduction and a bibliography, about the Harris Matrix, which is a tool for archaeologists for the display of stratigraphic information in the form of a diagram.